1989
DOI: 10.1007/bf02411404
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the diurnal/circadian expression of the chlorophyll a/b-binding proteins in leaves of tomato and other dicotyledonous and monocotyledonous plant species

Abstract: Diurnal oscillations of steady-state mRNA levels encoding the chlorophyll a/b-binding proteins were monitored inLycopersicon esculentum, Glycine max, Phaseolus vulgaris, P. aureus, P. coccineus, Pisum sativum, Sinapis alba, Hordeum vulgare, Triticum aestivum andZea mays. In these plant speciescab mRNA accumulation increases and decreases periodically indicating i) that the expression of the genes for chlorophyll a/b-binding proteins (cab genes) is controlled by a circadian rhythm, and ii) that the rhythm is wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 42 publications
5
43
1
Order By: Relevance
“…Patterns 3 and 4, characterized by an increase at the beginning of the day and a decrease in the second part of the day, are similar to those found for the small subunit of ribulose 1,5-bisphosphate carboxylase in pea (13), for light-harvesting complex protein in tobacco (25), for cab in tomato (9,18), and for cab9 1 R in Petunia (28). All of these previously described rhythms are circadian.…”
Section: Diumal Rhythmicity In Spot Intensitysupporting
confidence: 70%
See 1 more Smart Citation
“…Patterns 3 and 4, characterized by an increase at the beginning of the day and a decrease in the second part of the day, are similar to those found for the small subunit of ribulose 1,5-bisphosphate carboxylase in pea (13), for light-harvesting complex protein in tobacco (25), for cab in tomato (9,18), and for cab9 1 R in Petunia (28). All of these previously described rhythms are circadian.…”
Section: Diumal Rhythmicity In Spot Intensitysupporting
confidence: 70%
“…On the other hand, several recent studies have demonstrated diurnal or circadian rhythmicity in the level of specific mRNAs (8,9,13,18,21,25,28 (6). Gels were prepared for fluorography using Amplify (Amersham, UK) and exposed to preflashed Kodak X-Omat AR film, 48 Leaves of S. alba were harvested and their mRNA analyzed at the beginning (0 h), middle (4 h), and end of the day (8 h) as well as three times during the following night (12,16, and 20 h).…”
Section: Plant Materialsmentioning
confidence: 99%
“…To provide a comparison with a gene of known function, we identified the P. nil Cab gene as a well-characterized gene known to be regulated by light and an endogenous rhythm (Piechulla, 1988;Meyer et al, 1989;Millar and Kay, 1991 O'Neilletal. Plant Physiol.…”
Section: Dark-and Circadian-regulated Transcriptsmentioning
confidence: 99%
“…The involvement of circadian rhythms in light-regulated gene expression of plants is widely recognized (Kloppstech, 1985;Guilano et al, 1988;Nagy et al, 1988;Piechulla, 1988;Meyer et al, 1989;Millar and Kay, 1991). In the majority of studies of circadian-regulated gene expression in plants, light rather than darkness is the extemal signal influencing the amplitude of cycling mRNA levels (Guilano et al, 1988;Taylor, 1989).…”
Section: Ldentification Of Mrnas Associated With Photoperiodicmentioning
confidence: 99%
See 1 more Smart Citation